Numerical and experimental analysis of heat transfer in turbulent flow channels with two-dimensional ribs. (22nd January 2015) - Wang, H.T.; Lee, W.B.; Chan, J.; To, S.
Abstract: The repeated ribs surfaces are known for their effective enhancement of heat transfer, which is widely demanded in many scientific and industrial applications. In this paper, further improvements were made by the introduction of a textured asymmetric arc rib structure, on which arrays of secondary micro grooves are superimposed onto a primary asymmetric surface. Numerical simulation has been carried out on the turbulent force convection flow in a single-phase channel with two-dimension (2D) ribbed internal surface in the range of Reynolds number from 20, 000 to 60, 000. A uniform heat flux is applied on the external surface of channel. In contrast to the conventional optimized symmetric triangular rib, the advanced compound rib could improve the performance of heat transfer while minimizes the pressure drop. These improvements are closely correlated to the promotion of the separated flow which could reattach the channel surface. Since the geometry of the novel compound rib is difficult to fabricate by conventional means, ultra-precision raster milling (UPRM) is used to generate these micro-structures. According to prediction of numerical simulation, the experimental cooling works have been designed and conducted for the considered shaped ribs with the significant dimensionless pitch of 5 and 6. A good agreement was found between the simulation and experimental results. Highlights: The advanced two-dimensional compound ribs for heat transfer are concerned. Effects of geometry and surface roughness on heat transfer and pressure drop are observed. Effects of arrangements of ribs on heat transfer and pressure drop are studied. The optimal various shaped ribs are verified by experiments. It is suggested to use the advanced ribs in heat exchanger devices.